Research on hot deformation behavior and microstructure characterization of the NiTi alloy fabricated by wire arc additive manufacturing - Xiaochun Chen; Hongsheng Chen; Huihui Nie; Wenxian Wang; Liuwei Zheng; Jun Zhou (Journal of Materials Research and Technology)
This study investigates the hot deformation behavior and microstructural evolution of wire arc additive manufactured (WAAMed) NiTi alloy. Hot deformation tests were conducted within a temperature range of 750–900 °C and a strain rate range of 0.01–5 s−1, achieving a height reduction of up to 50%. The Strain-Compensated Arrhenius-Type (SCAT) model and deformation processing maps were developed. The microstructures of compression specimens at strain rates of 0.01 s−1 and temperatures of 750–900 °C were characterized. The results demonstrate that the flow stress of WAAMed NiTi alloys increases with increasing strain rate and decreases with increasing deformation temperature. The calculated values from the SCAT model align closely with the experimental values, indicating a reliable analysis with high prediction accuracy. Flow instability region expands as the degree of deformation increases, and the optimal processing windows for the studied alloy are concentrated within the range of 800–900 °C and 0.01–0.05 s−1. In the deformed WAAMed NiTi alloys, the proportion of low-angle grain boundaries is around 70% and the recrystallized grain fraction remains below 15%. This is attributed to the predominance of dynamic recovery behavior in the softening mechanism. Discontinuous dynamic recrystallization and continuous dynamic recrystallization as auxiliary softening mechanisms are also involved in the softening of NiTi alloys, leading to a steady state of flow behavior.